Different modes of translation for hid, grim and sickle mRNAs in Drosophila. - Vazquez-Pianzola, P.; Hernandez, G.; Suter, B.; Rivera-Pomar, R. (Cell Death and Differentiation, 2007)
Protein synthesis is inhibited during apoptosis. However, the translation of many mRNAs still proceeds driven by internal ribosome entry sites (IRESs). Here we show that the 5'UTR of hid and grim mRNAs promote translation of uncapped-mRNA reporters in cell-free embryonic extracts and that hid and grim mRNA 5'UTRs drive IRES-mediated translation. The translation of capped-reporters proceeds in the presence of cap competitor and in extracts where cap-dependent translation is impaired. We show that the endogenous hid and grim mRNAs are present in polysomes of heat-shocked embryos, indicating that cap recognition is not required for translation. In contrast, sickle mRNA is translated in a cap-dependent manner in all these assays. Our results show that IRES-dependent initiation may play a role in the translation of Drosophila proapoptotic genes and suggest a variety of regulatory pathways.